Government information in the opening pages of the press section in reference - Méndez Nieto, Antonio; Paniagua Rojano, Francisco Javier; León Gross, Teodoro (Historia y Comunicación Social, 2018)
In this article, the origin of the informations published by media about the national, regional and local governments is analyzed, with the purpose of identifying the different channels used by its communications offices. The main conclusion is the ease of the institutions to protagonize that priviledged area in the media studied. Near seven out of ten opening news studied proceded from the communications offices, above all from public events, appearances, statements, and press conferences. That means they belong to what is called ‘call journalism’, with information available to everybody in contrast to the ‘differenciated journalism’. In this case, the treatment of the news will establish the peculiarities that show each newspaper with the publication of them. Besides, most of these informations are supported in only one source, which denotes that the total credibility is given to the emisor of the administration or that the lack of resources has a negative impact in an essential labor to the quality of the product as the contrast of the information. To develop the research, the technique of analysis of content has been used. In particular, it has been studied 558 opening section news published in two national papers —El País and El Mundo— and two local ones — Sur and Málaga Hoy—, have been analyzed during 2010.